PENINGKATAN KETERAMPILAN PROBLEM SOLVING, COMMUNICATION DAN COLLABORATION DENGAN PENDEKATAN SCIENTIFIC TIPE LEARNING TOGETHER - Aulia Almas Agustin Hidayat; Jailani Jailani; Nadya Amalia Juana (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2022)
Techonological developments 5.0 requires all people to have soft skill that should they develop so that they are not left and be able to adressing a social and educational issues. So this research focused on mathematic learning that applied a learning together-type scientific approach to improve 21 st century skills which include problem solving, communication and collaboration. This research is a quantitative study pseudo-experiments. The subjects in this study were 32 class VIII students at SMPN 7 Batang. The data collection techniques used are observation, questionnaires, interview and tests. The result of this study showed that mathematics learing with a learning together type scientific approach had increase a significant  in terms of the achievment of KD pretest by 38,3 % and posttest 77,08%. Using that result can show that problem solving skills have improved. Meanwhile, communication and collaboration skills are measured by giving quetionnaires and improving before and after treatment. So that the implementation of a learning together type scientific approach can develop 21 century skills.